2007
DOI: 10.1021/jp0678002
|View full text |Cite
|
Sign up to set email alerts
|

Search of Nature of Planar Chirality for Pendent Benzodiazacoronands in the Solid State:  NMR, X-ray, and DFT Studies

Abstract: In this work, we report the structural studies on the solid state of two benzodiazacoronads that form chiral and achiral crystals. Crystals have to be considered as a two-component system consisting of an organic unit and a water molecule in 1:1 ratio. Both components play an important role in the crystal structure. The strong (O-H...O, N-H...O) and weak (C-H...O) intermolecular hydrogen bonds are responsible for phase organization and, in consequence, formation of chiral or achiral crystals. The alignment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…The NMR data were consistent with a rapid exchange of water molecules between available sites in the crystal lattice. Similar observation was reported by Pacholczyk et al who searched the reversible water exchange in the crystal lattice of benzodiazacoronads [24]. In all cited papers the presence (or absence) of water in the crystal framework is indirectly monitored by detection of heteronuclei ( 13 C, 15 N etc.).…”
Section: Resultssupporting
confidence: 71%
“…The NMR data were consistent with a rapid exchange of water molecules between available sites in the crystal lattice. Similar observation was reported by Pacholczyk et al who searched the reversible water exchange in the crystal lattice of benzodiazacoronads [24]. In all cited papers the presence (or absence) of water in the crystal framework is indirectly monitored by detection of heteronuclei ( 13 C, 15 N etc.).…”
Section: Resultssupporting
confidence: 71%
“…We found that, for all crystal structures studied, CS bond and macrocyclic NH protons are directed inward toward the macrocyclic cavity, whereas the lariat NH proton is directed outward. Such a well-defined structural preorganization of amide groups was already observed in crystal structures of various di, tri-, and pentamide ,, UCs, and hence it is a rather common feature for these kinds of macrocyclic compounds. Analysis of the Hirshfeld fingerprint plots reveals some additional common features (Figure ).…”
Section: Resultsmentioning
confidence: 53%
“…On the basis of previous study, we assume that for 1d only water molecules are occluded in the crystal lattice. Solid state NMR spectra of a similar benzodiazacoronand host molecule without organic solvent guests but containing water molecules in the crystal lattice were reported by Pacholczyk et al 5 Fig. 2 displays 15 N CP/MAS spectra of HGC of 1 recorded at a spinning rate of 8 kHz.…”
Section: Resultsmentioning
confidence: 62%
“…As we reported elsewhere, the benzodiazacoronands under investigation possess unique stereochemical properties and belong to a class of compounds with planar chirality. 1,5 In the course of our study we have found that atropoisomers of benzodiazacoronands can exist in solution provided that one of the two independent requirements is satisfied: first, the presence of a large intraannular group that cannot pass through the macroring plane and thus defines its top and bottom sides; second, the presence of a group that differentiates between the left and right sides of the macrocycle (Scheme 1).…”
Section: Introductionmentioning
confidence: 87%